2015
DOI: 10.1186/s12950-015-0101-4
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I contributes to the innate immune response after cerebral ischemia

Abstract: BackgroundFocal cerebral ischemia induces an inflammatory response that when exacerbated contributes to deleterious outcomes. The molecular basis regarding the regulation of the innate immune response after focal cerebral ischemia remains poorly understood.MethodsIn this study we examined the expression of retinoic acid-inducible gene (RIG)-like receptor-I (RIG-I) and its involvement in regulating inflammation after ischemia in the brain of rats subjected to middle cerebral artery occlusion (MCAO). In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Our results show that the overexpression of RIG-I triggers IRF3 phosphorylation and IFN-β transcription per se . Interestingly, it has been reported that RIG-I is also overexpressed in the hippocampus after focal cerebral hypoxia 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the overexpression of RIG-I triggers IRF3 phosphorylation and IFN-β transcription per se . Interestingly, it has been reported that RIG-I is also overexpressed in the hippocampus after focal cerebral hypoxia 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For immunoblot analysis of NLRP1 and ASC proteins from clots of nine different patients, protein was extracted and resolved as described in ( Brand et al, 2015 ). Briefly, equal amounts of protein lysates (20 μg of total protein) were resolved in 4–20% Criterion TGX Stain-Free precasted gels (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Protein levels of inflammasome signaling proteins were determined in the cytosolic and mitochondrial fractions as described in [ 7 ]. Briefly, protein lysates were resolved in 10–20% Criterion TGX Stain-Free precasted gels (Bio-Rad), using antibodies (1:1000 dilution) to NLRC4 (Novus Biologicals, cat# NBP2–41124), caspase-1 (Novus Biologicals, cat# NB100–56565), caspase-11 (Novus Biologicals, cat# MAB8648), ASC (Santa Cruz, cat# sc-271054), IL-1β (Cell Signaling, cat# 12242S), IL-18 (Abcam, cat# ab71495), HSP60 (Cell Signaling, cat#12165) and β-actin (Sigma Aldric, cat# A5441).…”
Section: Methodsmentioning
confidence: 99%